2014
DOI: 10.1021/la500682t
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of CO2 and H2O Partitioning between Na–Montmorillonite and Variably Wet Supercritical Carbon Dioxide

Abstract: Shale formations play fundamental roles in large-scale geologic carbon sequestration (GCS) aimed primarily to mitigate climate change and in smaller-scale GCS targeted mainly for CO2-enhanced gas recovery operations. Reactive components of shales include expandable clays, such as montmorillonites and mixed-layer illite/smectite clays. In this study, in situ X-ray diffraction (XRD) and in situ infrared (IR) spectroscopy were used to investigate the swelling/shrinkage and H2O/CO2 sorption of Na(+)-exchanged mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
202
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(259 citation statements)
references
References 52 publications
56
202
1
Order By: Relevance
“…However, it is critical as it results in cation hydration at lower relative humidity, i.e., clay hydration, compared to the non-CO 2 case. This hypothesis is in agreement with Loring et al (2014) who showed an initial steep increase in CO 2 interlayer concentrations with increasing water contents in the range between 0 and 1 W, followed by a decrease towards higher hydration states.…”
Section: Molecular Dynamics Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is critical as it results in cation hydration at lower relative humidity, i.e., clay hydration, compared to the non-CO 2 case. This hypothesis is in agreement with Loring et al (2014) who showed an initial steep increase in CO 2 interlayer concentrations with increasing water contents in the range between 0 and 1 W, followed by a decrease towards higher hydration states.…”
Section: Molecular Dynamics Studiessupporting
confidence: 93%
“…These measurements were performed at 50°C and pressures up to 18 MPa. Loring et al (2014), using X-ray diffraction and IR spectroscopy at 50°C and 9 MPa on Na-SWy-2, studied relative CO 2 uptake as a function of clay water content, and demonstrated a steep increase in CO 2 interlayer contents at low water saturations. This steep increase seems to correspond to a step in hydration from 0 to 1 W. With an increase in water content, this CO 2 concentration decreases and almost disappears when the clay interlayer distance moves to 2 W. This clearly demonstrates that the interlayer CO 2 uptake capacity is strongly related to the water content.…”
Section: Co 2 Sorption On Clay Mineralsmentioning
confidence: 99%
“…This behavior indicates that the addition or removal of nonstructural or interlayer space H 2 O can be recognized based on the areas of peaks near 3450 cm − 1 and 3350 cm −1 . Recent work by Loring et al (2014) quantitatively correlated Na + -Mt clay mineral expansion with adsorbed H 2 O concentration in the presence of supercritical CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, hydrated and relatively dehydrated Na + -STx-1 were exposed to anhydrous CO 2 and monitored with Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) to discern mechanistic information for CO 2 interaction with the Na + -STx-1 and examine any CO 2 -induced perturbations in vibrational modes associated with interlayer water or the silicate framework. The interaction of CO 2 with Na-STx-1 was investigated at pressures up to 5.9 MPa, a range that lies between CO 2 pressures of b120 Torr (b0.016 MPa) (Fripiat et al, 1974) and 9 MPa (Loring et al, 2012(Loring et al, , 2014 explored in previous FTIR studies on clay mineral-CO 2 interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent research on CO 2 intercalation, however, provides an accurate molecular description of CO 2 for evaluating surface tension, contact angles, capillary flow, snap-off (or the disconnection of a continuous stream of the non-wetting CO 2 when it passes through pore constrictions, a form of residual trapping), and related phenomena associated with CO 2 trapping [84]. Intercalation could provide additional storage capacity for CO 2 in clay layers on reservoir rock coatings and in the caprock [51,58], and could also be a mechanism for controlling potential leakage [58,100,101]. Investigations into these aspects of scCO 2 behavior, at elevated pressures and temperatures characteristic of geologic carbon sequestration, have only recently begun [99,102].…”
Section: Modelsmentioning
confidence: 99%